2017
DOI: 10.3389/fpsyg.2016.02027
|View full text |Cite
|
Sign up to set email alerts
|

The Freedom to Pursue Happiness: Belief in Free Will Predicts Life Satisfaction and Positive Affect among Chinese Adolescents

Abstract: A small amount of research has examined the association between the belief in free will and subjective well-being (SWB) among Western laypersons from individualist cultures. However, no study has examined this association among participants from collectivist cultures (e.g., Eastern Asian cultures). Therefore, in this study, we explored this association among two large, independent cohorts of Chinese adolescents (N1 = 1,660; N2 = 639; high school students). The belief in free will was measured by a self-reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 38 publications
5
16
0
2
Order By: Relevance
“…The PANAS has been widely used among clinical and nonclinical samples, and its internal reliability in previous studies has been reported as excellent (Merz et al., ; Morrison & Heimberg, ). The PANAS has a higher reliability and validation for Chinese version (Li, Wang, Zhao, Kong, & Li, ; Li, Yang, Liu, & Wang, ). Cronbach's α for the PA in this study was .81.…”
Section: Methodsmentioning
confidence: 99%
“…The PANAS has been widely used among clinical and nonclinical samples, and its internal reliability in previous studies has been reported as excellent (Merz et al., ; Morrison & Heimberg, ). The PANAS has a higher reliability and validation for Chinese version (Li, Wang, Zhao, Kong, & Li, ; Li, Yang, Liu, & Wang, ). Cronbach's α for the PA in this study was .81.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of the previous research findings presented in the theoretical background above, i.e. that belief in free will is associated with higher well-being (life satisfaction and higher positive affect) (Crescioni et al, 2016;Li et al, 2017), we hypothesized as follows: H1: Belief in free will increases the level of both cognitive and affective well-being, and decreases ill-being (poor health condition).…”
Section: The Present Researchmentioning
confidence: 99%
“…At a minimum, it seems that free will beliefs and their variants (e.g., feelings of agency, perceptions of choice) are related to well‐being, happiness, and intrinsic motivation (Crescioni, Baumeister, Ainsworth, Ent, & Lambert, ; Leotti, Iyengar, & Ochsner, ; Ryan & Deci, ), and recent evidence suggests that these associations are not specific to western cultural contexts (Li, Wang, Zhao, Kong, & Li, ). Moreover, correlations exist between free will beliefs and “success” measures that have been associated with self‐discipline and self‐control, such as better job performance (Stillman et al, ), and better academic performance (Feldman, Chandrashekar, & Wong, ).…”
Section: Self‐controlmentioning
confidence: 99%